RHODODENDRON MEAGAII, A NEW SPECIES OF RHODODENDRON SUBGENUS VIREYA (ERICACEAE) FROM PAPUA, INDONESIA - Yasper Michael Mambrasar; Prima W. K. Hutabarat (Research Center for Biology, 2018)
MAMBRASAR, Y. M. & HUTABARAT, P. W. K. 2018. Rhododendron meagaii, a new species of Rhododendron subgenus Vireya (Ericaceae) from Papua, Indonesia. Reinwardtia 17(2): 97‒100. ‒‒ Rhododendron meagaii, is described and illustrated as a new species in subgenus Vireya (Ericaceae) from Mount Salju, District of Abenaho, Yalimo Regency, Papua Province, Indonesia. Characters distinguishing this new species from related species are discussed.